2013
DOI: 10.1177/1350650113484212
|View full text |Cite
|
Sign up to set email alerts
|

Braking performance and influence of microstructure of advanced cast irons for heavy goods vehicle brake discs

Abstract: It is well known that truck brakes dissipate several megajoules of energy every few seconds, which leads to high thermal stresses in the rubbing parts. Therefore, premature failure by cracking of truck brake discs is a matter of major concern. Improving the design and material of brake discs may enhance braking performance. This study focuses on the latter aspect and was carried out with the aim of developing new material solutions for increasing disc lifespan. To do so, braking experiments were conducted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…46 Such numerical finite element models allow simulations of repeated brake cycles but still need to be calibrated and validated with experimental studies on wear, friction and crack propagation. 710 Numerical analysis of crack growth under thermomechanical conditions has also been performed. 11…”
Section: Introductionmentioning
confidence: 99%
“…46 Such numerical finite element models allow simulations of repeated brake cycles but still need to be calibrated and validated with experimental studies on wear, friction and crack propagation. 710 Numerical analysis of crack growth under thermomechanical conditions has also been performed. 11…”
Section: Introductionmentioning
confidence: 99%
“…The test results after applying the dependences describing measurement point (2)(3)(4)(5), and the dependence of the speed of change (6) shown in Table 1. Based on the results, it was found that the most sensitive diagnostic parameter defined the dynamics of change for assessment of wear on the friction pads, obtained for the measurement of vibration acceleration Y 2 for all measurement points.…”
Section: Analysis Of the Results In The Amplitude Domainmentioning
confidence: 99%
“…Most of the articles raise the problems abrasive wear [4,14], but noise and vibration to disrupt the process of braking and comfort during this process [12]. There are many models that describe the vibrations generated by the braking systems which include Rudolph and Popp model [17], North [16] and Millner [21] (flutter binary model In contrast, a separate issue is the brake vibroacoustic diagnostics designed to diagnose selected brake components.…”
Section: Introductionmentioning
confidence: 99%
“…The work presents examples of uneven wear of friction linings such as higher wear on the outer radius of the disc relative to the inner radius of the disc, edge defects and cracking or tearing of the entire lining parts from the bearing plate. In this respect, works are underway on such a selection of the friction pair materials as to ensure a compromise among the costs of manufacturing (additional thermal and chemical processes when making the casts of the brake discs), the component wear and the friction mechanical properties of the friction pair, as described in [1,3,10,13,14,42]. On the other hand, [7,11,37] presents problems related to friction models and friction wear modeling of brake system components based on operational tests.…”
Section: Introductionmentioning
confidence: 99%